2013
DOI: 10.1021/bm400537w
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Amphiphilic Macromolecules with Variable Lipophilicity and Stereochemistry Modulate Inhibition of Oxidized Low-Density Lipoprotein Uptake

Abstract: Amphiphilic macromolecules (AMs) based on carbohydrate domains functionalized with poly(ethylene glycol) can inhibit the uptake of oxidized low density lipoprotein (oxLDL) and counteract foam cell formation, a key characteristic of early atherogenesis. To investigate the influence of lipophilicity and stereochemistry on the AMs' physicochemical and biological properties, mucic acid-based AMs bearing four aliphatic chains (2a) and tartaric acid-based AMs bearing two (2b and 2l) and four aliphatic chains (2g and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…As anticipated, increased inhibitory efficacy directly correlated to hydrophobic chain length for ether-linked AMs. Previous studies also found that larger and more hydrophobic sugar derivatives resulted in higher levels of oxLDL uptake inhibition [12, 30]. This result is likely due to a higher affinity binding to the hydrophobic domain of SR binding pockets.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…As anticipated, increased inhibitory efficacy directly correlated to hydrophobic chain length for ether-linked AMs. Previous studies also found that larger and more hydrophobic sugar derivatives resulted in higher levels of oxLDL uptake inhibition [12, 30]. This result is likely due to a higher affinity binding to the hydrophobic domain of SR binding pockets.…”
Section: Resultsmentioning
confidence: 72%
“…[10, 11] Detailed studies have shown that seemingly minor changes in the stereochemistry, degree of branching, and/or hydrophobicity of the aliphatic chains have a considerable effect on bioactivity. [9, 12, 13] Molecular modeling studies further suggested that AMs competitively inhibit oxLDL uptake by SRs via electrostatic and hydrophobic interactions with SR binding domains. [14] The 3D conformation of AMs in aqueous conditions, specifically the presentation of the hydrophobic arms, appears to be critically important for this inhibition efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…AMs were synthesized as previously described (19,26,34,35) and fabricated into kinetically assembled fluorescent NPs via flash nanoprecipitation (16,17). NP shell structures are depicted in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…M12P5, T12P5-meso, and T12P5-(L) were prepared as previously published [18, 27]. The synthetic scheme of T(12-O)P5 has been reported previously; however, extremely low yield (~10%) for the alkylation step using dibenzyl L-tartrate has limited its further investigation and evaluation as an atherosclerotic therapeutic [14].…”
Section: Resultsmentioning
confidence: 99%
“…Amphiphilic polymers M12P5 [18], T12P5-meso [27], and T12P5-(L) [27] were prepared as previously published and discussed. These AMP systems are referred to as M12P5 or T12P5, in which M and T denotes mucic acid and tartaric acid, respectively, 12 refers to the number of carbon atoms of each aliphatic chain, P stands for PEG, and 5 indicates molecular weight of the PEG in kDa.…”
Section: Methodsmentioning
confidence: 99%